2001
DOI: 10.1017/s0967026201003249
|View full text |Cite
|
Sign up to set email alerts
|

Thermal acclimation in the marine diatom Chaetoceros calcitrans (Bacillariophyceae)

Abstract: Thermal acclimation following changes from 6 mC to 15 mC and from 15 mC to 25 mC was investigated in the diatom Chaetoceros calcitrans. Cell division rate increased with temperature. Cellular carbon showed a slight decrease with an increase in temperature from 6 mC to 15 mC but showed no further change with an increase to 25 mC. Cells grown at 6 mC had low levels of light-harvesting components and a high carotenoid to chlorophyll a (Chla) ratio due to an increase in abundance of photoprotective pigments. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 0 publications
3
45
0
Order By: Relevance
“…5), the other species were not able to acclimate their light-harvesting capacity at extreme temperatures after at least 1 wk of acclimation. Anning et al (2001) described an increase of the ratio E/E k in the marine diatom Chaetoceros calcitrans at low temperature, as we observed particularly for S. marinoi and L. chlorophorum and more generally for all tested species. This confirms the apparent similarity of acclimation at low temperature and high irradiance.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…5), the other species were not able to acclimate their light-harvesting capacity at extreme temperatures after at least 1 wk of acclimation. Anning et al (2001) described an increase of the ratio E/E k in the marine diatom Chaetoceros calcitrans at low temperature, as we observed particularly for S. marinoi and L. chlorophorum and more generally for all tested species. This confirms the apparent similarity of acclimation at low temperature and high irradiance.…”
Section: Discussionsupporting
confidence: 82%
“…A decrease in chlorophyll content is a typical algal response to high irradiance, along with increased content of photoprotective carotenoids whose function is to dissipate excess energy. Several previous studies have shown that acclimation to low temperature mimics adaptation to high irradiance (Anning et al 2001, El-Sabaawi & Harrison 2006.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The decrease in auto-fluorescence intensity of coldadapted Micromonas (Supplementary Figure S3) suggests a reduction in chlorophyll content with decreasing temperatures as previously reported (Claquin et al, 2008). Several studies pointed out the similarity of photoacclimation trends at low temperatures to those at high irradiance (Anning et al, 2001;El-Sabaawi and Harrison, 2006;Claquin et al, 2008). Reports on the effect of light intensity evidenced the importance of this factor in regulating algal host-virus interactions (Waters and Chan, 1982;Bratbak et al, 1998;Brown et al, 2007;Baudoux and Brussaard, 2008).…”
Section: Discussionsupporting
confidence: 74%
“…4). The data shows that the average monthly P max values covary with temperature and peak in August concurrent with the temperature peak, which indicates that temperature directly affects P max (Anning et al 2001) due to enzyme-driven processes. Temperature also has an indirect effect on PP in that higher temperatures increase remineralization rates and thereby increase nutrient availability for phytoplankton production (Kemp and Boynton 1984).…”
Section: Relevance To Modelling Of Carbon Flow In Dynamic Ecosystemsmentioning
confidence: 92%